2017
DOI: 10.4238/gmr16029681
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and population structure analysis reveals diversity by mutations in Lasiodiplodia theobromae with distinct sources of selection

Abstract: ABSTRACT. Lasiodiplodia theobromae is a plant pathogen with a worldwide distribution, with low host specificity, causing stem cankers, dieback diseases, and fruit rot in several species of plants. In coconut, this pathogen is reported as the etiological agent of "coconut leaf blight" (CLB) disease, causing several losses in fruit production. The CLB is an important disease for this crop in Brazil. In our study, we used a phylogeographic approach through the molecular characterization of the translation elongat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
1
13
0
2
Order By: Relevance
“…The lack of diversity found in this study emphasizes the low genetic diversity of the pathogen in northeastern Brazil. This is in contrast with results from population genetics of L. theobromae from coconut trees in Brazil and other countries based on EF1‐α sequence analysis (Santos et al ., ). In that study, relatively high levels of genetic diversity were observed in populations from northeastern and southeastern Brazil.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The lack of diversity found in this study emphasizes the low genetic diversity of the pathogen in northeastern Brazil. This is in contrast with results from population genetics of L. theobromae from coconut trees in Brazil and other countries based on EF1‐α sequence analysis (Santos et al ., ). In that study, relatively high levels of genetic diversity were observed in populations from northeastern and southeastern Brazil.…”
Section: Discussionmentioning
confidence: 97%
“…In that study, relatively high levels of genetic diversity were observed in populations from northeastern and southeastern Brazil. However, according to those authors, the variability of L. theobromae haplotypes could be associated with selection pressures experienced by the pathogen due to high host diversity and control management strategies adopted by different regions in Brazil (Santos et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions between plant genotypes and fungal isolates throughout the evolution of living beings can bring harm to the host. It is possible setting effective disease control strategies when the variations between different pathogen isolates are known (SANTOS et al, 2017b). A practical example of it can be seen when fungi with pathogenic potential keep their ancestral ability to explore other hosts as endophytes.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogeographic studies about fungi, although scarce, may contribute to the knowledge about the pathogen diversity and help understanding the geographical distribution of genealogical lineages, mainly of the ones within and among closely-related species (AVISE, 2000;SANTOS et al, 2017b). The literature still lacks studies relating the geographic and phylogenetic distribution of the fungal species A. caricae.…”
Section: Introductionmentioning
confidence: 99%